Real-life experience on effectiveness and safety of dupilumab in adult patients with moderate-to-severe atopic dermatitis. (4th July 2021) - Fargnoli, M. C.; Esposito, M.; Ferrucci, S.; Girolomoni, G.; Offidani, A.; Patrizi, A.; Peris, K.; Costanzo, A.; Malara, G.; Pellacani, G.; Romanelli, M.; Amerio, P.; et al.
Abstract: Background: Dupilumab, a fully human monoclonal antibody targeting the alpha subunit of IL-4 was recently approved for the treatment of moderate-to-severe atopic dermatitis (AD) in adult patients. Objective: To assess dupilumab effectiveness and safety in adults with moderate-to-severe AD in a real-life Italian multicentre retrospective cohort. Methods: Adult moderate-to-severe AD patients, referring to 39 Italian centers, received dupilumab in the context of a national patient access program. Disease assessment was performed at baseline, after 4 and 16 weeks of treatment using Eczema-Area-and-Severity-Index (EASI) score, itch and sleep numerical-rating-score (itch-NRS, sleep-NRS) and Dermatology-Life-Quality-Index (DLQI). Results: A total of 109 (71 M/38F) patients was studied. There was a significant reduction in EASI score, itch-NRS, sleep-NRS and DLQI from baseline to week 4 and a further significant decline to week 16. EASI 50, EASI75 and EASI90 were achieved by 59.6%, 28.4% and 9.3% of patients at 4 weeks and by 87.2%, 60.6% and 32.4% of them at 16 weeks, respectively. Adverse events were experienced by 19.2% (21/109) of the patients and they were all mild in intensity, being conjunctivitis the most common side effect. Conclusions: Dupilumab significantly improved disease severity, pruritus, sleep loss and quality of life with an acceptable safety profile.